(untitled) (Bangladesh Journal of Plant Taxonomy, 2018)
Five DNA barcodes were tested for identification and discrimination of Lavendula dentata L., Mentha longifolia (L.) Huds. and Mentha × piperita L. New DNA barcodes have been registered for L. dentata from Taif, Saudi Arabia. The separate clading of L. dentata and M. longifolia through the phylogenic analyses proved their endemism to Saudi Arabia. The phylogenetic trees revealed from the ITS2, matK and trnH data demonstrated that all Mentha species formed monophyletic clusters except hybrid M. × piperita from Taif which formed separate clades distinguishing it from the two parents; M. aquatica L. and M. spicata L. DNA barcoding could be considered as a good approach for distinguishing and identifying the mint plants, though it was not possible to confirm the relationship between hybrids and their putative parents.